Nexuses Between Solumedrol and Dexamethasone in Moderate to Severe Covid Disease - Muhammad Ahmad, Qasim Nawaz Sahi, Mehwish Kiran, Arslan Iqbal, Muhammad Mohsin Farooq, Hafiz Muhammad Rizwan, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Covid 19 is a disease caused by a virus belonging to SARS Co V2 family of viruses. It primarily effects the lungs resulting in inflammation and pneumonia. Objectives: The main objective of the study is to compare the outcomes and efficacy of solumedrol and dexamethasone in moderate to severe COVID disease. Material and methods: This cross sectional study was conducted in Central Park Medical College and Teaching Hospital, Lahore and the duration of this study was from August 2021 to March 2022. The data was collected from 100 COVID-19 patients diagnosed with moderate to severe condition of the diseases. The data was collected through non-probability consecutive sampling technique. Results: The data was collected from 100 patients of moderate to severe COVID-19 condition. There were 35 patients in group I and 65 patients’ group II. The mean age for dexamethasone (group II) was 55.41 ± 10.4 years and solumedrol (group I) was 56.86 ± 9.3 years. Conclusion: It is concluded that both drugs dexamethasone and solumedrol are effective in improving clinical and biochemical parameters of moderate to severe covid 19 disease. Keywords: COVID-19, Patients, Inflammation, Markers, Lungs, Pneumonia